A 4-Part Strategy to Engage Frontline Nurses in Cultural Humility. (December 2021) - Virkstis, Katherine; Whitemarsh, Karl; Rewers, Lauren; Paiewonsky, Allyson
Abstract : Although many clinical leaders use the cultural competency model to help clinicians deliver equitable care, evidence on the model's effectiveness is mixed. In this article, the authors propose that nursing leaders adopt cultural humility as a framework that better positions nurses to build trust, engage patients in their care, and improve health outcomes. This article outlines 4 strategies that leaders can use to actively engage staff in cultural humility and support the cultural transformation required to mitigate the impact of clinician bias in care delivery.